Cervical cancer in women in Norway – epidemiology and prevention - Pałac, Renata; Mielnik, Aneta; Cipora, Elżbieta (Journal of Education, Health and Sport, 2025)
Introduction. In accordance with the guidelines of the World Health Organisation (WHO) as part of the Global Strategy to Accelerate the Elimination of Cervical Cancer, the Norwegian Institute of Public Health coordinates the implementation of primary and secondary prevention measures, aiming to achieve the near-total elimination of this cancer in the general female population in Norway within the next fifteen years. The aim of this study is to present the current epidemiological situation of women with cervical cancer in Norway and the prevention of this cancer. Materials and methods. The study involved a review and analysis of literature from the Cancer in Norway database from 2023 and 2024, as well as data published by: Folkehelseinstituttet - FHI (from 2020-2025), Årsrapport, Screeningaktivitet og resultater fra Livmorhalsprogrammet (from 2023 and 2024), Helsedirektoratet Livmorhalskreft – pakkeforløp (from 2022), Helsenorge –Livmorhalskreft (from 2025), Kreftregisteret (from 2022-2025). Results. Every year, approximately 25,000 Norwegian women are diagnosed with human papillomavirus (HPV) infection, which, as a result of persistent infections, is responsible for the development of dysplastic changes and cervical cancer. In 2024, 269 new cases of cervical cancer were reported, most of them in the early stages of the disease, and the incidence rate was 9.4 per 100,000, showing a significant downward trend compared to previous years. The average age of women at diagnosis was 48, and the disease rarely affected women under the age of 25. Conclusions. Norway’s experience shows that comprehensive preventive measures significantly contribute to reducing morbidity and mortality from cervical cancer. This model confirms that consistent implementation of primary and secondary prevention strategies can lead to long-term improvements in women’s health and serve as a model for other countries.